Single‐institution study of correlations between skeletal muscle mass, its density, and clinical outcomes in non‐small cell lung cancer patients treated with first‐line chemotherapy. Issue 12 (27th September 2018) - Cortellini, Alessio; Palumbo, Pierpaolo; Porzio, Giampiero; Verna, Lucilla; Giordano, Aldo V.; Masciocchi, Carlo; Parisi, Alessandro; Cannita, Katia; Ficorella, Corrado; Bozzetti, Federico
Abstract : Background: Sarcopenia and muscle tissue degradation are hallmarks of the majority of chronic diseases, including non‐small cell lung cancer (NSCLC). A computed tomography scan could be an easy modality to estimate the skeletal muscle mass through cross‐sectional image analysis at the level of the third lumbar vertebra. Methods: Baseline skeletal muscle mass (SMM) was evaluated through the skeletal muscle index (SMI), together with skeletal muscle radiodensity (SMD), in NSCLC patients undergoing first‐line chemotherapy to evaluate correlations with safety and clinical outcomes. When SMIs at different time points were available, further comparison was made between patients with worse and improved SMIs. Results: Among 81 stage IV NSCLC patients, 28 had low SMM and 23 had low SMD. There were no significant differences in univariate analysis of progression‐free survival (PFS) between patients with baseline low and non‐low SMM ( P = 0.06388) or between patients with low and non‐low SMD ( P = 0.9126). Baseline low SMM, however, proved a significant predictor of shorter PFS in multivariate analysis (hazard ratio 0.54, 95% confidence interval 0.31–0.93; P = 0.0278), but not low SMD. There were no differences in overall survival (OS) between patients with baseline low and non‐low SMM or low and non‐low SMD. No differences in PFS and OS between evaluable patients with worse or improved SMI were found. A significant difference in hematological toxicities between patients with baseline low and non‐low SMM ( P = 0.0358) was observed. Conclusions: Low SMM is predictive of shorter PFS, while consecutive changes in muscular mass do not seem to be a predictor of PFS or OS. The role of muscle radiodensity remains a matter of debate.